2016
DOI: 10.1016/j.virol.2016.09.020
|View full text |Cite
|
Sign up to set email alerts
|

The HPV16 E7 oncoprotein increases the expression of Oct3/4 and stemness-related genes and augments cell self-renewal

Abstract: Oct3/4 is a transcription factor involved in maintenance of the pluripotency and self-renewal of stem cells. The E7 oncoprotein and 17β-estradiol (E) are key factors in cervical carcinogenesis. In the present study, we aimed to investigate the effect of the HPV16 E7 oncoprotein and E on the expression pattern of Oct3/4, Sox2, Nanog and Fgf4. We also determined whether the E7 oncoprotein is associated with cell self-renewal. The results showed that Oct3/4, Sox2, Nanog and Fgf4 were upregulated by the E7 oncopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…We confirmed the up-regulation of Oct4 in cervical cancer tissues and cancer cells and we provide additional evidence that Oct4 is upregulated in HPV(+) tumors compared to HPV(-) ones. We also verified a causal relationship between the viral oncogenes and increased Oct4 levels in human immortalised keratinocytes and in the HPV(-) C33A cells, upon infection with the E6/ E7 oncogenes [27]. Hence, we hypothesise that both viral oncogenes affect the transcriptional program that regulates the endogenous expression of Oct4 in a direct or indirect manner.…”
Section: Discussionsupporting
confidence: 67%
“…We confirmed the up-regulation of Oct4 in cervical cancer tissues and cancer cells and we provide additional evidence that Oct4 is upregulated in HPV(+) tumors compared to HPV(-) ones. We also verified a causal relationship between the viral oncogenes and increased Oct4 levels in human immortalised keratinocytes and in the HPV(-) C33A cells, upon infection with the E6/ E7 oncogenes [27]. Hence, we hypothesise that both viral oncogenes affect the transcriptional program that regulates the endogenous expression of Oct4 in a direct or indirect manner.…”
Section: Discussionsupporting
confidence: 67%
“…After the viral DNA is integrated, it synthesizes the E6 and E7 oncoproteins that promote proliferation for TP53 degradation by E6 and pRB degradation by E7; it has been observed that the degradation of pRb leads to the overexpression of OCT3/4 and that the degradation of p53 leads to an increase in the expression of NANOG (65,66), and it is well known that NANOG can directly bind to the OCT3/4 gene promoter to induce its expression (67-69). Recently, it was observed that the E6 and E7 oncoproteins of HPV16 increase expression levels of a subset of stem cell marker genes, including OCT3/4, NANOG, and SOX2 both in vivo and in vitro and that cells expressing the E6 and E7 oncoprotein exhibit a greater self-renewal capacity (70,71). These data suggest that the E6 and E7 oncoproteins increase the self-renewal of cancer cells.…”
Section: Oct3/4 and E6 And E7 Oncoproteinsmentioning
confidence: 99%
“…Biochemical evidence which dates back to the initial understanding of the function of Oct4 demonstrated the ability of high-risk HPV E7 (similar oncoproteins such as adenovirus E1A) to directly interact and synergize with Oct4 for the activation of its target genes [ 59 , 60 ]. More recent evidence from transgenic animals suggests that E7 may also contribute to the transcriptional upregulation of Oct4 [ 61 ]. Furthermore, E7 was shown to epigenetically reprogram cells via the transcriptional activation of histone demethylases lysine (K)-specific demethylase 6A and 6B (KDM6A and KDM6B, respectively) [ 62 ].…”
Section: Mechanisms Of Enhancing Cellular Plasticitymentioning
confidence: 99%
“…Both pRb and p53 have been shown to be important gatekeepers during cellular reprogramming, and their absence significantly facilitates the process [ 50 , 51 , 53 , 56 ]. ( b ) Transcriptional upregulation of histone modifying enzymes: Upregulation of lysine (K)-specific demethylase 6A and 6B (KDM6A and KDM6B, respectively) mediated by the E7 oncogene of HPV16 leads to a reduction of repressive H3K27 chromatin marks and downstream activation of targets such as Hox genes [ 62 , 63 ]; ( c ) Transcriptional upregulation of stem cell-related transcription factors: the viral oncogenes E6 and E7 of high-risk types have been linked to the upregulation of pluripotency associated transcription factors—Oct4 [ 61 ], Hes family basic helix-loop-helix transcription factor 1 (Hes1) [ 67 ]. Infection with cutaneous papillomaviruses has also been linked to the upregulation of stem cell related genes [ 30 , 64 ].…”
Section: Figurementioning
confidence: 99%